Barbados : Seventh Review Under the Extended Fund Facility Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Despite significant economic shocks associated with the COVID-19 pandemic, twin natural disasters, and the war in Ukraine, Barbados has made good progress in implementing its Economic Recovery and Transformation (BERT) plan to restore fiscal and debt sustainability, rebuild reserves, and increase growth. International reserves increased to USD 1.5 billion at end-2021 supported by IFI loans. This, and a successful 2018-19 public debt restructuring, helped rebuild confidence in the country's macroeconomic framework. Economic growth is projected at 11 percent for 2022 premised on a robust recovery of tourism, which is expected to return to pre-pandemic levels by 2024. The outlook nonetheless remains highly uncertain, and risks are elevated, including from higher global commodity prices following the Russian invasion of Ukraine that are feeding into inflation. Since Barbados imports the bulk of its food and energy needs, the government has adopted temporary VAT caps on oil products to contain retail price increases (fiscal cost of 0.3 percent of GDP). While fiscal accommodation was needed to respond to the pandemic and natural disasters over the past two years, the authorities are committed to running primary surpluses from FY2022/23 onwards which need to reach 5-6 percent of GDP in three years, consistent with meeting the 60 percent of GDP debt target by FY2035/36.